Control of cytokine-driven eosinophil migratory behavior by TGF-beta-induced protein (TGFBI) and periostin. - Karina T Barretto; Calvin M Swanson; Christopher L Nguyen; Douglas S Annis; Stephane J Esnault; Deane F Mosher; Mats W Johansson (PLoS ONE)
Periostin, which is induced by interleukin (IL)-13, is an extracellular matrix (ECM) protein that supports αMβ2 integrin-mediated adhesion and migration of IL-5-stimulated eosinophils. Transforming growth factor (TGF)-β-induced protein (TGFBI) is a widely expressed periostin paralog known to support monocyte adhesion. Our objective was to compare eosinophil adhesion and migration on TGFBI and periostin in the presence of IL-5-family cytokines. Eosinophil adhesion after 1 h and random motility over 20 h in the presence of various concentrations of IL-5, IL-3, or granulocyte macrophage-colony stimulating factor (GM-CSF) were quantified in wells coated with various concentrations of TGFBI or periostin. Results were compared to video microscopy of eosinophils. Cytokine-stimulated eosinophils adhered equivalently well to TGFBI or periostin in a coating concentration-dependent manner. Adhesion was blocked by anti-αMβ2 and stimulated at the lowest concentration by GM-CSF. In the motility assay, periostin was more potent than TGFBI, the coating-concentration effect was bimodal, and IL-3 was the most potent cytokine. Video microscopy revealed that under the optimal coating condition of 5 μg/ml periostin, most eosinophils migrated persistently and were polarized and acorn-shaped with a ruffling forward edge and granules gathered together, in front of the nucleus. On 10 μg/ml periostin or TGFBI, more eosinophils adopted a flattened pancake morphology with dispersed granules and nuclear lobes, and slower migration. Conversion between acorn and pancake morphologies were observed. We conclude that TGFBI or periostin supports two modes of migration by IL-5 family cytokine-activated eosinophils. The rapid mode is favored by intermediate protein coatings and the slower by higher coating concentrations. We speculate that eosinophils move by haptotaxis up a gradient of adhesive ECM protein and then slow down to surveil the tissue.